Linguistic Image of DOM ‘home’ in Wojciech Piotrowicz’s Autobiographical Prose - Fedorowicz, Irena; Geben , Kinga (Vilnius University Open Series, 2021)
The aim of the article is to describe the concept of dom ‘home’ in Wojciech Piotrowicz’s idiolect by using the methodological assumptions of Lublin ethnolinguistics school. Research on which this paper is based consists of two main parts: we present the writer’s biography, which introduces a representative of the Polish intelligentsia in Lithuania, and an analysis of the concept of dom ‘home’. The presented biography emphasizes the origin and formation of the personality of the recognized writer and social and cultural activist, whose life is an example of the formation of the Polish intelligentsia in Lithuania. The subject of research is a textual data coming from his volume of memoirs, which contains the writer’s memories and reflections. The analysis of the dom ‘home’ concept focuses on two profiles: physical and symbolic, specific features were grouped onto facets. In the conclusions, we underline the specific character of home in Wojciech Piotrowicz’s autobiographical prose which has some differences comparing to home described in Polish, Lithuanian and Belarusian languages by EUROJOS project.